PERSPECTIVES OF NON-URBAN GENERAL PEDIATRICIANS ON DIAGNOSING AUTISM SPECTRUM DISORDER - Das, Jennifer (Paediatr Child Health, 2018)
BACKGROUND: Wait times for autism spectrum disorder (ASD) diagnosis contribute to delayed access to ASD interventions, which are most effective at young ages. General paediatricians (GPs) represent a potential resource for increasing diagnostic capacity and decreasing wait times for ASD diagnostic assessments. No current research has yet to solicit perspectives of non-urban GPs on ASD diagnosis. OBJECTIVES: The objective of this project was to explore the perspectives of GPs practicing in smaller Ontario communities regarding their diagnostic processes and their role in ASD diagnostic assessment. DESIGN/METHODS: We performed a qualitative study using thematic analysis of GPs’ experiences with cases of suspected ASD. GPs from three small/medium-sized Ontario communities (population range: 14,000–64,000) were recruited to provide variation in perspectives. Semi-structured interviews were conducted, transcribed, and coded. A preliminary theoretical framework was developed and sent to participants with a request for feedback (member checking). Feedback did not necessitate any significant changes to the framework. RESULTS: 14 GPs participated in interviews (7 from Community A, 4 from Community B, 3 from Community C). All participants considered ASD diagnosis to be in the GP’s scope of practice and part of their service to their community. Many sought out and self-funded additional ASD training as necessitated by their practices. Our framework identified three stages in the diagnosis of ASD: pre-assessment (gathering information prior to the first clinic visit), diagnosis, and service access. All of these stages are influenced by ecological factors including the individual patient/family, individual physician factors, factors reflecting the GP’s community group practice (i.e., how the group has decided its members will approach developmental referrals), and factors concerning the broader system of ASD care. CONCLUSION: GPs practicing in non-urban Ontario communities routinely diagnose ASD and see this as part of their scope of practice. Compared to their urban counterparts, they emphasized a stronger sense of responsibility to provide this service to their communities. Strategies aimed at increasing diagnostic capacity should target group practices, increase availability of ASD specific training programs, and improve efficiency of clinic visits through pre-clinic information gathering. Further research regarding accuracy of GP assessments is required.